High-intensity interval training, performance, and oxygen uptake kinetics in highly trained traditional rowers - Mujika, I.; Bourdillon, N.; De Txabarri, R. G.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Oxygen uptake kinetics (VO2kinetics) is a measure of an athlete`s capacity to respond to variations in energy demands. Faster VO2kinetics is associated with better performance in endurance sports, but optimal training methods to improve VO2kinetics remain unclear. This study compared the effects of 2 high-intensity interval-training (HIIT) programs on traditional rowing performance and VO2kinetics.